Construção de cenários ambientais a partir de indicadores da gestão dos resíduos sólidos urbanos no município de Paulo Afonso/BA - Santos Junior, Robério Satyro dos (2021)
The environmental problems resulting from the generation of solid waste become more evident over time, mainly due to large-scale consumption patterns, influenced by the capitalist economic system. As a result, there is a large production of solid waste in cities, causing social, economic and environmental problems. To mitigate such damages, it is necessary to create integrated management measures, which encompass several aspects related to the process, such as, for example, the creation of the Municipal Plan for Integrated Management of Solid Waste - PMGIRS, a document that gathers all the information, in a integrated approach on aspects of solid waste management. In the city of Paulo Afonso, state of Bahia, the problems with the integrated management of solid waste have resulted from the lack of a selective collection program that seeks to make a greater use of the collected waste, in addition to the development of a plan that includes all measures used in the management process. As a way of contributing to the definition of PMGIRS through information subsidies, a general objective of the research was to carry out the construction of environmental scenarios based on indicators of MSW management, ratifying the importance of introducing more consistent measures, such as, for example, a selective collection program. To this end, the following methodological instruments were used: bibliometric survey, in the search for works that addressed the theme on solid waste; Application of questionnaires and interviews with the main research agents (ARPA and SEMA); use of gravimetric composition to understand the characteristics of urban solid waste generated by the municipality; and finally, the construction of environmental scenarios for the management of MSW, with the methodology of systems dynamics. As an answer, it is evident that the generation of solid waste has a growth trend over the years, which urges the creation of measures that directly affect the problem, in the case of the city of Paulo Afonso / BA. The implementation of selective collection and measures involving recyclable material collectors becomes extremely important and would present changes in the social, environmental and economic context, as shown by the simulations carried out by the researched software. In light of this, the construction of environmental scenarios is of great importance for the composition of the PMGIRS prognosis, in addition to providing the greatest amount of information on the management of MSW, for the composition of the document. In this research, several information were collected that can assist in the construction of the PMGIRS in the city of Paulo Afonso / BA, ensuring that all legal aspects are met, as required by Law 12.305 / 2010, which deals with the National Solid Waste Policy.